Penukaran tanah wakaf masjid agung Semarang dalam perspektif fikih istibdal - Ahmad Furqon (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
Substitution of waqf land is one of nazir (waqf fund manager) efforts to make waqf lands managedmore productive. Semarang Mosque Welfare Council (BKM), as nazir, has made three substitutions ofSemarang Grand Mosque waqf lands. Those three-time substitutions leaved problems causing to poorresults of the waqf lands managed. This study is aimed at finding out the substitution process ofSemarang Grand Mosque waqf lands and the pespective of Istibdal Fiqh on substitutions of SemarangGrand Mosque waqf lands. This study is a case study. The data collection techniques are observation,interview, and documentation. The interview is conducted to parties who know the substitution caseof Semarang Grand Mosque waqf lands. The data collected are analyzed descriptively. The results of thisstudy are: 1) the first substitution of Semarang Grand Mosque waqf lands, made with PT Sambirejo, isnot based on in-depth research especially on land replacement. The party invited to conduct the transaction,Cipto Siswoyo from PT. Sambirejo, his testimony is categorized unacceptable due to fraud. 2) Thesecond substitution of Semarang Grand Mosque waqf lands, which is in the form of money to establishMa’had Aly, is less rocommended by fiqh scholars since the money value tends to decline, and isprone to corrupt and abuse. Moreover, Ma’had Aly has not established yet during the substitutionprocess happened in 2008 to 2016. 3) The third substitution of Semarang Grand Mosque waqf landsemploys substitute money used to purchase substitute lands. This is considered appropriate and theprice of the substitute lands refers to the market price.